Measurement of CP violation in the phase space of B±→K± π+ π- and B±→K± K+ K- decays. - Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Alvarez Cartelle, P; et al. (2013)
The charmless decays B±→K± π+ π- and B±→K± K+ K- are reconstructed using data, corresponding to an integrated luminosity of 1.0  fb(-1), collected by LHCb in 2011. The inclusive charge asymmetries of these modes are measured as ACP(B±→K± π+ π-)=0.032±0.008 (stat)±0.004 (syst)±0.007(J/ψK±) and ACP(B±→K± K+ K-)=-0.043±0.009 (stat)±0.003 (syst)±0.007(J/ψK±), where the third uncertainty is due to the CP asymmetry of the B±→J/ψK± reference mode. The significance of ACP(B±→K± K+ K-) exceeds three standard deviations and is the first evidence of an inclusive CP asymmetry in charmless three-body B decays. In addition to the inclusive CP asymmetries, larger asymmetries are observed in localized regions of phase space.